The Universe as an Open or Closed System: A Comparative Analysis of Scientific and Religious Perspectives - Goshu, Belay Sitotaw; Ridwan, Muhammad (Budapest International Research and Critics University, 2025)
The openness or closeness of the universe has long been a topic of discussion in both scientific and religious circles. Scientific theories in cosmology and quantum mechanics suggest an evolving and possibly infinite universe, while religious perspectives offer varied interpretations, often emphasizing divine purpose, interconnectedness, and ultimate destiny. Understanding this debate is crucial in addressing global challenges and fostering a more unified perspective on existence. Purpose: This study aims to explore the implications of an open or closed universe through scientific and religious perspectives, identifying areas of convergence and divergence. It examines how these views shape human consciousness, governance, and ethical responsibility toward planetary and interstellar sustainability. A qualitative comparative analysis was conducted using literature reviews of scientific theories, theological texts, and historical perspectives. Key scientific frameworks included thermodynamics, quantum mechanics, and astrophysics, while religious interpretations were drawn from Christianity, Islam, and other spiritual traditions. Findings: The analysis revealed that an open-system perspective aligns with both scientific discoveries—such as cosmic expansion and interstellar material exchange—and religious teachings that emphasize universal interconnectedness. A closed-system perspective, while useful in deterministic models, may limit broader explorations of human potential, intergalactic cooperation, and ethical governance. Conclusions: By fusing scientific discoveries with spiritual consciousness, an open-system paradigm promotes a transition from conflict-driven government to collaborative global and interplanetary stewardship. Recommendations: Policymakers, educators, and religious leaders should foster interdisciplinary dialogue, promote ethical space exploration, and develop frameworks for sustainable planetary and cosmic engagement.